(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Interactions with many clinically active therapeutic agents with deoxyribonucleic acid (DNA) are well studied and it expedites deciphering the structure of DNA and to investigate the pathological implication of those molecules in a living organism. The interaction of dextromethorphan hydrobromide (DEX) with calf thymus DNA (ct DNA) was studied employing UV absorption and fluorescence spectroscopic techniques. The binding affinity of DEX to DNA was calculated at different temperatures and the stoichiometry of binding was characterized to be about 1 dextromethorphan molecule per nucleotide. Hypochromic effect was found in the absorption spectra of dextromethorphan, and its wavelength had no shift in the presence of DNA indicating external binding mode of dextromethorphan to DNA. Quenching constants 3532 L/ mol and 12446L/ mol at 298 K and 308 K respectively with correlation co-efficient of 0.974 and 0.976, using Stern-Volmer equation and the quenching mechanism was found to be dynamic. Fluorescence spectroscopic results showed the quenching of fluorescence intensity of DEX in the presence of DNA, indicating the interaction between DEX and DNA. Based on this, hydrophobic interaction were found to play the dominating role in DEX-DNA binding and those binding forces also indicate the binding site of dextromethorphan to be in the minor groove of DNA. Bangladesh Pharmaceutical Journal 19(2): 197-205, 2016